Serotonin and Interleukin 10 Can Influence the Blood and Urine Viscosity in Gestational Diabetes Mellitus and Pregnancy-Specific Urinary Incontinence - França, Danielle Cristina Honório [UNESP]; Honorio-França, Adenilda Cristina; Silva, Kênia Maria Rezende; Alves, Fernanda Cristina Bérgamo [UNESP]; Bueno, Gabriela [UNESP]; Costa, Sarah Maria Barneze [UNESP]; Cotrim, Aron Carlos de Melo; Barbosa, Angélica Mércia Pascon [UNESP]; França, Eduardo Luzía; Rudge, Marilza Vieira Cunha [UNESP] (MDPI, 2023)
Serotonin and interleukin 10 (IL-10) may play a role in gestational diabetes mellitus. Hyperglycemic environment, the detrusor musculature of the bladder and pelvic floor muscles may become damaged, leading to urination problems and urine viscosity in pregnant women with gestational diabetes mellitus and pregnancy-specific urinary incontinence. Urine and blood samples were collected from pregnant women between 24 and 28 weeks of gestation. The serotonin concentration and cytokine IL-10 levels were evaluated in plasma and urine. In the total blood and urine, the viscosity was evaluated in the presence and absence of exogenous serotonin and IL-10. The plasma serotonin levels decreased, while the urine serotonin levels increased in the normoglycemic incontinent (NG-I), hyperglycemic continent (GDM-C), and hyperglycemic incontinent (GDM-I) groups. The IL-10 in the plasma decreased in the GDM-I group and was higher in the urine in the NG-I and GDM-I groups. The blood viscosity was higher, independently of urinary incontinence, in the GDM groups. The serotonin increased the blood viscosity from women with GDM-C and urine in the NG-I, GDM-C, and GDM-I groups. Blood and urine in the presence of IL-10 showed a similar viscosity in all groups studied. Also, no difference was observed in the viscosity in either the blood or urine when in the presence of serotonin and IL-10. These findings suggest that serotonin and IL-10 have the potential to reduce blood viscosity in pregnant women with gestational diabetes and specific urinary incontinence, maintaining values similar to those in normoglycemic women’s blood.
Keywords: cytokines; hormone; immunomodulation; involuntary loss of urine; rheology